The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10038-008-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction between pravastatin and olmesartan in relation to SLCO1B1 polymorphism

Abstract: The impact of SLCO1B1 polymorphism on the pharmacokinetics of olmesartan and on the pharmacokinetic interaction between pravastatin and olmesartan was investigated. On day 1, ten healthy volunteers took an oral dose (10 mg) of pravastatin. After a 3-day washout period, each subject received olmesartan medoxomil (10 mg) for 3 days. On day 8, they received olmesartan medoxomil (10 mg) and pravastatin (10 mg) concurrently, and pharmacokinetic profiles were compared with those in each single-dose phase with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
3
22
0
1
Order By: Relevance
“…In a study of polymorphisms of the gene for the transporter OATP1B1, SLCO1B1, the mean C max and AUC 0-24 of olmesartan tended to be higher in *15/*15 subjects than in *1b/*1b subjects, whereas the mean CL t/F in *15/*15 subjects was significantly lower than that in *1b/*1b subjects (Suwannakul et al, 2008). Other investigators did not confirm a role for polymorphisms in the SLCO1B1 gene and did not detect one for those in the gene encoding breast cancer resistance protein, ABCG2, but found that two singlenucleotide polymorphisms in the gene encoding mrp2, ABCC2, were associated with a greater olmesartan exposure .…”
Section: H Pharmacokinetic Pharmacogenomicsmentioning
confidence: 92%
“…In a study of polymorphisms of the gene for the transporter OATP1B1, SLCO1B1, the mean C max and AUC 0-24 of olmesartan tended to be higher in *15/*15 subjects than in *1b/*1b subjects, whereas the mean CL t/F in *15/*15 subjects was significantly lower than that in *1b/*1b subjects (Suwannakul et al, 2008). Other investigators did not confirm a role for polymorphisms in the SLCO1B1 gene and did not detect one for those in the gene encoding breast cancer resistance protein, ABCG2, but found that two singlenucleotide polymorphisms in the gene encoding mrp2, ABCC2, were associated with a greater olmesartan exposure .…”
Section: H Pharmacokinetic Pharmacogenomicsmentioning
confidence: 92%
“…In addition, the pharmacokinetics of atrasentan, ezetimibe, fexofenadine, irinotecan, lopinavir, olmesartan, and torsemide have shown associations with the SLCO1B1 genotype (Niemi et al, 2005c;Katz et al, 2006;Xiang et al, 2006;Han et al, 2008;Oswald et al, 2008;Suwannakul et al, 2008;Vormfelde et al, 2008;Werner et al, 2008;Han et al, 2009;Innocenti et al, 2009;Hartkoorn et al, 2010;Kohlrausch et al, 2010;Lubomirov et al, 2010;Sai et al, 2010;Werner et al, 2010). In general, the SLCO1B1 c.521TϾC variant (*5 or *15 haplotype) is associated with impaired hepatic uptake and increased plasma concentrations of most OATP1B1 substrates, whereas the SLCO1B1*1B haplotype is associated with an enhanced hepatic uptake and decreased plasma concentrations of some OATP1B1 substrates.…”
Section: Role Of Oatp1b1 In Hepatic Drug Uptakementioning
confidence: 99%
“…The mechanism of these changes has not yet been fully worked out. It is worth noting that the clinical relevance of MRP2 inhibition DDI is minimal in humans, with exposure levels reaching 121%-234% of those in normal subjects, depending on the drug considered (Chester et al, 2003;Suwannakul et al, 2008;Ieiri et al, 2009;Brennan et al, 2015;Davenport et al, 2015). Recently, the specificity of CPs I and III transport was studied using cells transfected with various transporters (Bednarczyk and Boiselle, 2016).…”
Section: Coproporphyrin As Endogenous In Vivo Probe For Oatp1bmentioning
confidence: 99%